DESIGNING AN INFORMATION SYSTEM FOR WEDDING ORGANIZER RENTAL SERVICES USING THE FCFS ALGORITHM AT ASSYIFA STUDIO - Riki Bayu Andhika; Yovi Pratama; Ronald Naibaho (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Assyifa studio Assyifa Studio, Muara Sabak Timur District is a service provider business to organize an event that is already professional. Assyifa Studio has encountered problems with the system that is running, including frequent errors in data collection of booking schedules that cause schedule collisions between customers so that rental services often occur. the wedding organizer was booked at the same time. Because the administration is still recording bookings using tickets or notes. The purpose of this study is to analyze the system that is running, in order to overcome the problems faced at Assyifa studio, by designing a wedding Organizer rental service information system design using the FCFS algorithm on Assyifa studio, to provide convenience in conducting online transactions and help book the Wedding Organizer schedule and improve services in receiving orders for Wedding Organizer services.